2021
DOI: 10.31235/osf.io/5pqug
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What are the active ingredients of ‘arts in health’ activities? Development of the INgredients iN ArTs in hEalth (INNATE) Framework

Abstract: Background: There is a scarcity of research concerning what it is about arts engagement that may activate causal mechanisms leading to effects on health and wellbeing outcomes: their active ingredients. Further, the limited studies that do exist have tended to be relevant to specific contexts and types of art forms. The aim of this study was to carry out a comprehensive mapping of potential active ingredients, construct a shared language, and propose a framework and toolkit to support the design, implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…(Female, aged [35][36][37][38][39] Our quantitative work also revealed that some of the psychological symptoms of long Covid may have roots in biological pathways. Symptoms of depression and anxiety emerge almost immediately after infection in both 'short' and long Covid sufferers, but interestingly, we found that those who developed long Covid had much higher initial increases in depressive symptoms than those with short Covid (83).…”
Section: Long Covidmentioning
confidence: 62%
See 3 more Smart Citations
“…(Female, aged [35][36][37][38][39] Our quantitative work also revealed that some of the psychological symptoms of long Covid may have roots in biological pathways. Symptoms of depression and anxiety emerge almost immediately after infection in both 'short' and long Covid sufferers, but interestingly, we found that those who developed long Covid had much higher initial increases in depressive symptoms than those with short Covid (83).…”
Section: Long Covidmentioning
confidence: 62%
“…Meanwhile, we found no association in longitudinal patterns of engagement with those living in remote areas who had traditionally been more engaged, suggesting that for a period of time, home confinement enabled or encouraged more engagement for certain groups (80). For example, in our qualitative interviews, we found that these enablers included having more free time, a change to normal routines, and the availability of arts resources online (81). However, at the same time, these could also be barriers for those who found digital arts formats inaccessible or who preferred to engage in person (81).…”
Section: Social Cultural and Community Engagementmentioning
confidence: 64%
See 2 more Smart Citations
“…In our current work, we investigate if this presumably better experience can also impact the well-being effects of art experience. Given that previous work has shown that better aesthetic experiences also lead to enhanced well-being effects of such art experiences (Mastandrea, 2019;Trupp et al, 2023;Warran et al, 2022), we assume that multimodal aesthetic experiences should lead to more well-being gain. Thus, our goal and central research question were to investigate how an ecologically paired multimodal art experience can improve aesthetic experience and therefore well-being benefits compared to a single modality art experience.…”
mentioning
confidence: 99%